In women's Arms: Croatian Ethnology from 1945-1991 - Potkonjak, Sanja (2011)
Inside the tradition of ethnological thought in Croatia we can distinctly separate a critical branch of thought originating in the second half of the 20th century. This “movement” started as early as 1948, and was aimed at critical understanding and consistent questioning of methodological and epistemological limitations of Croatian ethnological “practice”. In a broad time span, works of Vera Stein Erlich, Dunja Rihtman Auguštin, Olga Supek (Zupan) and Lydia Sklevicky, point to the emergence of female voice in Croatian ethnology which has been self-fashioned as post-traditional. Even though we cannot speak of a unique professional community – a school of thought or a ‘scientific club’ of sort, those women ethnologists/anthropologists were focused on a ‘dialogue’ or negotiation between revolutionary ‘pupils’ and ‘normal’ science. Embeddedness in the tradition of thought in respect to which the authors defined their critical (epistemological) and temporal detachment, was marked in their works by the questioning of retro-utopian orientation on disciplinary subject lost in history, and later by the critique of the discipline which methodologically and epistemologically hibernated in relation to its own contemporaneity. The above mentioned authors have, with different intensity, questioned in their works the role of women in society with the intention to turn the marginal subject of scientific interest into one of the programs of post-traditional ethnography.
Projekt MZOS
ENG